ANALISA DAN KINERJA JARINGAN KABEL BACKBONE FIBER OPTIC LINK PRIMARY DAN REDUNDANT GATOT SUBROTO - BANDUNG 5SELATAN PT XYZ - Friyatno Halomoan Rumapea; Syam Gunawan (Journal of Research and Publication Innovation, 2024)
The internet has become a major daily need for society at this time, so with the development of technology and the large demand for internet communications, it demands greater bandwidth capacity and faster transmission. This encourages internet telecommunications service providers to provide network infrastructure capable of serving customers with good quality with adequate device capacity. So the author carried out an analysis and performance of the primary and redundant backbone fiber optic link cable network Gatot Subroto - South Bandung Pt Xyz. The technique used is to analyze attenuation, dispersion, link power budget, rise time budget, and BER. The research objective is to determine the performance of the backbone link network using the help of OptiSystem software. To determine the calculation of link power budget parameters, rise time budget, dispersion, availability and Bit error rate. The results of the research show that the performance of the Gatot Subroto - South Bandung and South Bandung - Gatot Subroto backbone link networks is quite good. As a recommendation in The backbone infrastructure development process requires quite good expertise and requires design in the form of initial calculations, power link budget calculations, power margin calculations to obtain more optimal network performance.